An assessment of the ocular tear film in patients with thyroid disorders - Alanazi SA (Dove Medical Press, 2019)
Saud A Alanazi,1 Abdullah A Alomran,1 Ali Abusharha,1 Raied Fagehi,1 Naji J Al-Johani,2 Gamal A El-Hiti,1 Ali M Masmali11Cornea Research Chair, Department of Optometry, College of Applied Medical Sciences, King Saud University, Riyadh 11433, Saudi Arabia; 2Comprehensive Cancer Center, Department of Endocrinology and Thyroid Oncology, King Fahad Medical City, Riyadh, Saudi ArabiaObjective: To investigate the ocular tear film in patients with thyroid disorders using various tests.Methods: The study involved the assessment of the ocular tear film in 20 patients with thyroid disorders (6 men and 14 women) aged 18–43 years (mean±standard deviation=34.3±3.2 years). An age-matched control group consisting of 20 subjects (8 males and 12 females) ranging in age from 18 to 43 years (31.3±2.9 years) was also examined under similar conditions. All patients completed the Ocular Surface Disease Index questionnaire, followed by the tear ferning test within the right eye. A phenol red thread test was carried out 10 mins later followed by the fluorescein tear break-up test with a 10-min gap between the tests being implemented.Results: The median score for the Ocular Surface Disease Index (P<0.05) showed the condition of mild dry eyes [median (IQR)=15.5 (21.9)] in patients with thyroid disorders compared to the control group [5.6 (3.6)]. The mean score for the phenol red thread test within both the right and left eyes showed acceptable tear volumes of 11.7±8.1 and 10.5±7.4 mm, respectively, but this was much lower (P<0.05) compared to those recorded within the control group (22.2±6.5 and 20.7±5.2 mm, respectively). In addition, the mean for the tear break-up time (P<0.05) scores in both eyes within the patients with thyroid disorders revealed a certain degree of eye dryness (4.9±1.6 and 4.2±1.9 s), while the control group showed normal eye scores (13.2±2.6 and 12.3±2.2 s). The median score for tear ferning grades showed eye dryness [2.0 (2.2)] within the study group and normal eyes [1.2 (0.9)] within the control group.Conclusions: Patients with thyroid disorders have a significant level of eye dryness compared to normal eye subjects.Keywords: dry eye, thyroid gland disorders, phenol red thread test, tear break-up time test, tear ferning patterns, ocular tear film